Localization of SK2 channels relative to excitatory synaptic sites in the mouse developing Purkinje cells - Carmen eBallesteros-Merino; José eMartínez-Hernández; Carolina eAguado; Masahiko eWatanabe; John eAdelman; Rafael eLujan (Frontiers Media S.A., 2014)
Small-conductance, Ca2+-activated K+ (SK) channels regulate neuronal excitability in a variety of ways. To understand their roles in different neuronal subtypes it is important to determine their precise subcellular distribution. Here, we used biochemical, light microscopy immunohistochemical and immunoelectron microscopy techniques, combined with quantitative approaches, to reveal the expression and subcellular localization patterns of SK2 in the developing cerebellum. Using western blots, the SK2 protein showed a progressive increase during postnatal development. At the light microscopic level, SK2 immunoreactivity was very prominent in the developing Purkinje cells, particularly in the molecular layer. Electron microscopy revealed that throughout development SK2 was mostly detected at the extrasynaptic and perisynaptic plasma membrane of dendritic shafts and dendritic spines of Purkinje cells. However, there was some localization at axon terminals as well. Quantitative analyses and 3D reconstructions further revealed a progressive developmental change of SK2 on the surface of Purkinje cells from dendritic shafts to dendritic spines. Together, these results indicate that SK2 channels undergo dynamic spatial regulation during cerebellar development, and this process is associated with the formation and maturation of excitatory synaptic contacts to Purkinje cells.